Managing menu innovation in a saturated market: an empirical evidence from restaurant chains in Malaysia - Mazalan Mifli; Rahmat Hashim; Artinah Zainal (2015)
This paper presents the empirical results of a recently concluded research study about managing menu innovation in a consumer market that has reached to its saturation level. Such market condition resulting in increased competition and, therefore, a need for increased innovation is essential. In this study, an investigation was carried in substantiating the effect of market saturation toward the relationship between innovation orientations and new menu innovation process. The region of Klang Valley was chosen as the study setting for its dynamic and matured consumer foodservice market. In this investigation, the theoretical conceptualization and the empirical validation of the proposed menu innovation process as a second-order hierarchical model along with the moderating variable of market saturation as first-order constructs were first advanced using both Statistical Package for Social Science (SPSS version 19) and partial least squares. Empirically, the measurement and structural models of this study confirmed adequate estimations based on partial least squares path modeling parameters. In line with the strength of partial least squares to explain complex relationships, the use of path modeling has made it possible to advance the theoretical contribution to this study. The results show that the moderating effect of market saturation on the link between the exogenous and endogenous variables found to have a medium effect size (f2Â¼0.289) and significant at <0.05). The findings point to managerial challenges in shaping competition as evidence of radical innovations is still being pursued, although slightly weaken. This study, apart from its contribution to the model development of menu innovation process, has meaningful implications for restaurateurs to stay afloat in such a market condition.